2009
DOI: 10.1090/s0002-9947-09-04738-2
|View full text |Cite
|
Sign up to set email alerts
|

Nonautonomous Kolmogorov parabolic equations with unbounded coefficients

Abstract: Abstract. We study a class of elliptic operators A with unbounded coefficients defined in I × R d for some unbounded interval I ⊂ R. We prove that, for any s ∈ I, the Cauchy problem u(s,admits a unique bounded classical solution u. This allows to associate an evolution family {G(t, s)} with A, in a natural way. We study the main properties of this evolution family and prove gradient estimates for the function G(t, s)f . Under suitable assumptions, we show that there exists an evolution system of measures for {… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
141
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(141 citation statements)
references
References 21 publications
0
141
0
Order By: Relevance
“…As it has been proved in [32] the following Hypothesis 2.2 provides us with a sufficient criterion for the existence of a Borel measure as in the statement of Theorem 2.1.…”
Section: A First Core For the Operator G Pmentioning
confidence: 88%
See 4 more Smart Citations
“…As it has been proved in [32] the following Hypothesis 2.2 provides us with a sufficient criterion for the existence of a Borel measure as in the statement of Theorem 2.1.…”
Section: A First Core For the Operator G Pmentioning
confidence: 88%
“…Recently, in [32] part of the results in [17,25,26] have been extended to more general nonautonomous Kolmogorov operators with analytical tools. In particular, under rather general assumptions on the smoothness of the coefficients of the operator A and assuming the existence of a Lyapunov function of A (see the forthcoming Hypothesis 1.1(iii)), it has been shown that an evolution operator (that we still denote by P (s, r)) can be associated with the nonautonomous elliptic operator A such that, for any bounded and continuous function ϕ, P (s, r)ϕ is the value at t of the unique classical solution to (1.2).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations